Cardiac Magnetic Resonance in Heart Failure: Diagnostic and Prognostic Assessments - Sara Pezzini; Francesca Daus; Giorgia Galli; Andrea Farina; Gabriele Fragasso; Roberto Spoladore (Journal of Cardiovascular Development and Disease, 2025)
With its high spatial resolution and tissue contrast, cardiac magnetic resonance (CMR) is an extremely flexible imaging technique that enables a thorough morphological and functional evaluation of the heart and vascular system. From diagnosis to treatment planning and risk assessment, CMR is being utilized more and more in the evaluation of patients with heart failure (HF). CMR offers a variety of techniques for characterizing myocardial tissue, aiding in identifying the cause of HF, as well as whole-heart cine imaging for precise measurement of biventricular dimensions and function. The aim of this review is to the describe the role of CMR in chronic heart failure, in particular for diagnostic workups, differential diagnosis, and information on how CMR influences treatment planning choices.